2021
DOI: 10.1097/cce.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms in Relatives of Critically Ill Patients: A Longitudinal Cohort Study

Abstract: OBJECTIVES: To explore the psychologic impact of an ICU stay on relatives and to determine patient and relative factors, including their pre-ICU mental health status, associated with psychologic symptoms 3 months after ICU admission. DESIGN: A prospective, exploratory, longitudinal cohort study. SETTING: A 12-bed ICU in a Dutch tertiary teaching hospital. PATIENTS: The relatives of ICU patients admitted between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Family members and the critically ill ICU patient, as individuals, are affected by the critical illness and ICU care (Rydwik et al, 2021) but in different ways and with different timeframes (Ågren et al, 2019;Rengel et al, 2019). How the mental and physical life was before the ICU is of course crucial to the way the individuals are affected (de Ridder et al, 2021;Geense et al, 2020). The fact that family members as a unit affect each other mentally when something is happening within the unit, develops the family unit and protects it from major disruption (Epstein et al, 1978;McGoldrick et al, 2013).…”
Section: Results Discussionmentioning
confidence: 99%
“…Family members and the critically ill ICU patient, as individuals, are affected by the critical illness and ICU care (Rydwik et al, 2021) but in different ways and with different timeframes (Ågren et al, 2019;Rengel et al, 2019). How the mental and physical life was before the ICU is of course crucial to the way the individuals are affected (de Ridder et al, 2021;Geense et al, 2020). The fact that family members as a unit affect each other mentally when something is happening within the unit, develops the family unit and protects it from major disruption (Epstein et al, 1978;McGoldrick et al, 2013).…”
Section: Results Discussionmentioning
confidence: 99%
“…The family’s prior family functioning and family hardiness were not known in this study, important to acknowledge that all persons are individual and process their experience differently. As one study has shown, the need for follow-up has different timeframes and some need more follow-up than others [ 32 ] Studies have shown that families reporting increased symptoms of depression and anxiety due to their experience of the ICU reported symptoms of these issues even prior to admission [ 33 ]. Several studies have reported positive intervention effects of family-centered care, and nurses’ communication and psychosocial care were considered essential components of nursing interventions in the ICU [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…depression and anxiety due to their experience of the ICU reported symptoms of these issues even prior to admission [33]. Several studies have reported positive intervention effects of family-centered care, and nurses' communication and psychosocial care were considered essential components of nursing interventions in the ICU [34,35].…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, measurement of mental health symptoms among relatives only after 3 months may not have been sufficient, as patients’ rehabilitation trajectories vary. Similar studies collected longitudinal data before admission, as the mental health status of relatives before ICU admission may be an important predictor of mental health outcomes of relatives after the patient’s ICU stay ( 37 ) and following admission ( 18 , 38 , 39 ). Furthermore, as shown in this Dutch study, facilitating the process of participation was shown to increase the odds of a neutral to positive attitude toward participation, which probably will facilitate participation in daily ICU practice.…”
Section: Strengths and Limitationsmentioning
confidence: 99%